Polycyclic Aromatic Hydrocarbons in Grilled Beef and Chicken and Their Reduction Through Various Treatments - Farhadian, Afsaneh (2010)
The International Agency for research on cancer (IARC) and the Environmental Protection Agency (EPA) have classified some polycyclic aromatic hydrocarbons (PAHs) are probably and possibly carcinogenic to humans. This research has been conducted to test for availability of three of PAHs in grilled beef and chicken and assess their levels, and to evaluate the potential for reducing their levels, if any, through different treatments. The specific objectives are i) to validate the method of extraction of the PAHs (fluoranthene, benzo(b)fluoranthene and benzo(a)pyrene) from meat matrix, ii) to examine the effects of different grilling methods on generation of PAHs in meat, iii) to assess the effects of different marinating procedures on the generation of PAHs in meat, iv) to explore the effects of meat preheating and wrapping on generation of PAHs in meat, and v) to evaluate the sensory properties of treated (marinated, preheated and wrapped) grilled meat. Tandem solid-phase extraction (SPE), were validated for sample preparation and clean up. A high performance liquid chromatography (HPLC) with fluorescence detector was used for PAHs analysis. For achievement of the second objective, nine types of Malaysian grilled meat dishes were analyzed for PAHs. The highest total concentration of the three PAHs, 103.32 ng/g, was found in the charcoal-grilled beef satay. For fulfillment of the second objective, the charcoal, gas and oven grilling methods were compared. The total concentrations of PAHs produced in the meat were significantly (p<0.05) different between the three grilling methods and were 132.64 ng/g, 15.00 ng/g, and 7.14ng/g in the charcoal-, gas-, and oven-grilled dishes, respectively. Since the highest total concentrations of PAHs were detected in beef and chicken satay, these dishes were chosen for the next objectives. For third objective, seven marinade treatments at four time intervals (0, 4, 8 and 12 hr) were applied on meat samples before charcoal grilling. The study showed that the highest reductions in PAH generation were achieved by the acidic marinade treatments for the chicken (81%) and beef (70%) satay samples. Acidic marinating using lemon juice at a concentration of 1.2% for 4 hr marinating time affected significantly (p<0.05) lower total PAHs generation. Therefore, this marinade treatment was applied on the meat samples in order to study the effects of preheating methods, steam and microwave heating, on reducing the duration of charcoal-grilling and PAHs generation. The results demonstrated that steam-heating lead to reductions in PAH generation ranging from 46 to 100% and from 51 to 100% respectively in the beef and chicken samples. On the other side, microwave-heating resulted in reductions in PAH generation in the beef and chicken samples ranging from 34 to 100% and from 60 to 100%, respectively. The effects of wrapping using aluminum foil and banana leaf during charcoal-grilling on the levels of PAHs produced, Showed the reductions of PAH generation in the beef and chicken samples fell within the ranges of 39-100% and 72-100%, respectively, when aluminum foil was used as the wrapping material. However, reductions fell within the ranges of 32-100% and 81-100%, respectively, upon use of banana leaves as the wrapping material. The results of sensory evaluation confirmed that the preheating, wrapping and acidic marinating treatments were successful methods for reducing food contamination with the studied PAHs.